(untitled) (Asian Journal of Social Science Studies, 2019)
City identity can be defined as the soul of a city and it plays an important role in increasing urban competitiveness (Gao, 2010). Recently, urban distinct features including historic heritages have been badly damaged in the rapid process of urbanization and economic growth, generating a crisis of city identity loss in urban planning, especially in small/medium cities where many have become similar in recent decades. The issue of a crisis in city identity has become established globally. With recognition of identity value, and the rising of people’s physical, as well as, psychological living demands in seeking a sense of belonging, extensive attention has been given to protection of city characteristics and identity recovery by both policy makers and urban designers (Li and Wang, 2006). Particularly, in China, rapid urbanization as a result of economic growth has led to city identity becoming reduced (Li, 2005). Homogenization and standardization in urban planning is very common and prominent in small/medium size cities in China. Many cities face a crisis where historic character and original identity is disappearing gradually and inevitably (Akkar Ercan, 2016). The principle aim of this paper is to discuss what is urban identity crisis and to explore it causes. In targeting this proposal, the following 2 questions and issues may need to be taken into consideration: 1. What is the definition and composition of the City identity? 2. What is the city identity crisis, including its causes and consequences? This requires systematic research on both literature review and world-wide case studies to explore the the city identity crisis and this may provide comprehensive, instructive, and operational design guide for shaping a ‘visible’ city’s identity, enhancing its uniqueness and further contributing to the solution for city identity crisis in China.